Probiotics to prevent and treat acute diarrhea in children (Archives of Pediatrics of Uruguay, 2020)
Probiotics from fermented products have been used since ancient times. They are living microorganisms, which, at appropriate levels, can provide health benefits.Among the benefits of probiotics, the most broadly studied has been the effect on children with acute diarrhea. There is extensive literature regarding the use of probiotics for the treatment and prevention of acute infectious diarrhea, for the prevention of nosocomial diarrhea and for antibiotic-caused diarrhea. The studies show heterogeneous methodologies and mixed results, even contradictory. For their interpretation, it is essential to take into account the probiotic strains used, the doses administered and the characteristics of the patients tested.There is evidence of the benefit of some probiotics strains in the treatment and prevention of acute diarrhea in children. Several Clinical Practice Guidelines recommend them. In Uruguay, there is little supply of these products, and the information available is scarce, which makes them difficult to prescribe.In the present document, we review the existing published scientific evidence regarding the use of probiotics in children with acute diarrhea.
Keywords: Probiotics; Dysentery; Child